(3bWQ GdfOi hHd GdUOis - (3GdCfUGQj GdeUQj, CHh eMeO, GHf gTGe, LeGd GdOjf, YHOGddg Hf jhSa Hf CMeO Hf YHOGddg, J (B761 (3g`s ((3Ydj Hf MSjf Hf YHO Gddgs)
(3ChdgG (B:s
(3GdcdeI bhd eaQO hgj GSe haYd hMQa aGdGSe jYQa HCd cGdQLds
(3BNQgG (B:s
(3hCeQ GdKdGKj cGbJO hGZR hGZRj HVegf hGVQH hGSJhj hGPgH HcSQgf ceG Hbj hGddg CYdes
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B: 4 / 147s
(3eYLe GdeDdajf(B: 2 / 305s
(3cTa GdXfhf(B: 2 / 1352s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
Keywords: (3GdfMhs